ANYTIME, ANYPLACE AND THE COMMUNITY COLLEGE: TEN EMERGING INSIGHTS - Milliron, Mark David; Prentice, Mary (Online Learning, 2004)
In today’s higher education world, asynchronous learning is the power tool. Moreover, the associated techniques for using asynchronous learning to support in-class and online instruction are bringing learning to life in new and exciting ways. This edition of the Journal of Asynchronous Learning Networks examines the role of these anytime, anyplace tools with a special focus on the characteristics of the community college movement—particularly the access, affordability, and outreach elements. Readers are treated to explorations of demographic trends, technological tools, and change-management strategies from well known researchers and practitioners. The conversation often ranges beyond community college, and that is with purpose. Community colleges are part of the broader family of education as well as a piece of the social and political fabric of the communities that they serve and thus deserve to be explored in this more complete context.